Hydroalkenylation: palladium catalyzed co-dimerization of unactivated alkenes. Issue 7 (17th February 2016) - Zargari, Nima; de Prevoisin, Gilles; Kim, Yeseul; Kaneshiro, Kelly; Runburg, Riley; Park, Jiwon; LaCroix, Kelsey; Narain, Reshma; Lee, Byung Do; Lee, Joo Ho; Jung, Kyung Woon
Graphical abstract: Abstract: A highly efficient co-dimerization of styrene and cyclopentene was developed in the presence of palladium and a BF3 source, selectively forming a new C–C bond. The complex [Pd(PPh3 )2 ] + BF4 − is believed to generate palladium hydride (Pd-H), which catalyzes the reaction between various styrenes and cyclopentene in excellent yields as single isomers. This co-catalytic system provides a new efficient C–C bond forming method.